PEMBUATAN REKAMAN KASET SEBAGAI MEDIA ALTERNATIF PADA MATERI SISTEM PERIODIK UNSUR UNTUK SISWA KELAS X SMA - Jumriana Rahayuningsih (Perspektif Pendidikan dan Keguruan, 2017)
The learning process will be more effective and efficient when supported by the appropriate media. Has conducted engineering research (eingineering) about the making of a tape recording as an alternative learning media on the material system periodically. The purpose of this study is to make a particular audio media tapes and to determine its feasibility as an alternative learning media in learning system periodic elements. This tape recording can be made in two versions of cassette tape version of relaxing with a duration of 60 minutes and tapes serious version that lasted 30 minutes. Based on data analysis using a Likert scale obtained as follows: for the cassette version of the students and teachers laid obtained kelayakkan same value is 3.5. and the values obtained tapes serious version of the feasibility of students and teachers respectively 3.7 and 3.6. Based on the above results it can be stated that the tape recording media is suitable as an alternative learning media students on the material elements of periodic system.